Effects of Simulated Microgravity on the Physiology of Stenotrophomonas maltophilia and Multiomic Analysis - Su, Xiaolei; Guo, Yinghua; Fang, Tingzheng; Jiang, Xuege; Wang, Dapeng; Li, Diangeng; Bai, Po; Zhang, Bin; Wang, Junfeng; Liu, Changting (Frontiers in Microbiology, 2021)
Many studies have shown that the space environment plays a pivotal role in changing the characteristics of conditional pathogens, especially their pathogenicity and virulence. However, S.maltophilia, a type of conditional pathogen that has shown to a gradual increase in clinical morbidity in recent years, has rarely been reported for its impact in space. In this study, S.maltophilia was exposed to a simulated microgravity environment in HARV bioreactors for 14 days, while the control group was exposed to the same bioreactors in a normal gravity environment. Then, combined phenotypic, genomic, transcriptomic and proteomic analyses were conducted to compare the influence of the simulated microgravity and normal gravity on S.maltophilia. The results showed that S.maltophilia in simulated microgravity displayed an increased growth rate, enhanced biofilm formation ability, increased swimming motility, and metabolic alterations compared with those of S.maltophilia in normal gravity and the original strain of S.maltophilia. COG annotation analysis indicated that the increased growth rate might be related to the upregulation of differentially expressed genes involved in energy metabolism and conversion, secondary metabolite biosynthesis, transport and catabolism, intracellular trafficking, secretion and vesicular transport. GO and KEGG enrichment analyses showed that the increased motility might be associated the upregulation of differentially expressed proteins involved in locomotion, localization, biological adhesion and binding, in accordance with the upregulated differentially expressed genes in cell motility according to COG classification, including pilP, pilM, flgE, flgG and ronN. Additionally, the increased biofilm formation ability might be associated with the upregulation of differentially expressed proteins involved in biofilm formation, the bacterial secretion system, biological adhesion and cell adhesion, which were shown to be regulated by the differentially expressed genes (chpB, chpC, rpoN, pilA, pilG, pilH, and pilJ) through the integration of transcriptomic and proteomic analyses. These results suggested that simulated microgravity might increase the level of corresponding functional proteins by upregulating related genes to alter physiological characteristics and modulate growth rate, motility, biofilm formation and metabolism. In conclusion, this study is the first general analysis of the phenotypic, genomic, transcriptomic, and proteomic changes in S.maltophilia under simulated microgravity and provides some suggestions for future studies of space microbiology.